McGrath MAC Versus Three-Dimensional Printed Video Laryngoscopes: A Randomized, Manikin-Simulated Noninferiority Controlled Study with Medical Students - Detoni, Pablo B. [UNESP]; Nascimento, Jedson S.; Araújo Azi, Liana M.T.; Pustilnik, Alexandre G.; Gusmão-Cunha, André; Módolo, Norma Sueli P. [UNESP]; Campos, Guilherme O.; de Almeida, Victor S.; Cambui, João Pedro M.M.; de Almeida, Vinicius S.; Alves, Rodrigo L. [UNESP] (Wolters Kluwer, 2025)
BACKGROUND: Proficiency in endotracheal intubation (ETI) is essential for medical professionals and its training should start at medical schools; however, large caseload may be required before achieving an acceptable success rate with direct laryngoscopy. Video laryngoscopy has proven to be an easier alternative for intubation with a faster learning curve, but its availability in medical training may be an issue due to its high market prices. We devised a low-cost 3-dimensionally printed video laryngoscope (3DVL) and performed a randomized trial to evaluate if the intubation success rate on the first attempt with this device is noninferior to a standard commercially available video laryngoscope (STVL). METHODS: Two hundred and nine medical students from 5 medical schools were enrolled and randomized to start with the STVL (McGrath MAC) or the 3DVL. Four stations (standard airway using the STVL/3DVL and difficult airway using the STVL/3DVL) were set to simulate ETI with standard Airway Management Trainer manikins (Laerdal Medical Ltd.). The noninferiority margin of 7.5% was defined for the success rate on the first attempt, considering the difference in proportions between the STVL (expected to be higher) and 3DVL groups. RESULTS: Regarding the standard airway station, 60.7% (n = 65) of the students successfully performed TI on the first attempt with the STVL within the established timeframe, compared to 36.3% (n = 37) of the students using the 3DVL. This represented a difference of 24.4% (95% confidence interval, 17.5%–31.3%). Considering the difficult airway station, the success rates on the first intubation attempt with the 2 VLs did not differ. CONCLUSIONS: The 3DVL was inferior in achieving first-attempt intubation when compared with the STVL with a difference in success rate >7.5% margin in simulated scenarios with medical students. Tracheal intubation might require a set of psychomotor skills for which the McGrath MAC device is superior to the low-cost alternative.